INTERACTION IN GEOSCIENCES EDUCATION AND SPATIAL DATA INFRASTRUCTURE DEVELOPMENT - EXAMPLE WESTERN BALKANS - ISSUES, IMPACT AND PROJECTS - Posloncec-Petric, Vesna; Bacic, Zeljko (International Multidisciplinary Scientific GeoConference SGEM, 2013)
Rapid development of GIS application in the last decade highlights two problems in the efficient usage of GIS technologies, entailing the usage of spatial data in general. The first problem was the lack of the concept in organizing the spatial data and the other problem lies in the fact that the subjects and the users didn't and still do not have enough knowledge about GIS and how to organize spatial data. Development of Spatial Data Infrastructure (SDI) concept can be understood as a response of society on the first problem, the growing demand for spatial information, respectively growing relevancy of spatial information for everyday's functioning of states, business and citizens. This is also valid for seven countries in the region of Western Balkans, which have joined their efforts to solve the issues and develop their national SDI's in line with INSPIRE through the execution of number of national and today regional INSPIRATION project.